MORATORIUM AND IMPACT ON BORROWERS AND BANKING INSTITUTIONS: A STUDY IN SEBERANG PERAI, PENANG - Farah Safura Muhammud; Nurul Syifa Bt Mahmad Zahri (International Journal of Accounting, Finance and Business, 2022)
The spread of the Covid-19 epidemic that hit the whole country has hampered the country’s economic resources. The problem is getting worse when some sectors have had to lay off some of their employees due to problems in paying salaries. This also disrupts the system of banking institutions when borrowers with financial problems are unable to repay monthly debts. As a result, the government has established a system of Moratorium or deferment of repayment to borrowers. The purpose of this research is first, to understand the concept of moratorium conducted in Seberang Perai, second, to study the factors of moratorium conducted in Seberang Perai Penang, and third objective is to analyse the awareness and importance of moratorium for residents in Seberang Jaya. This research is based on data obtained from 87 respondents in the district of Seberang Perai through the Google Form survey method. Data were analysed to assess and review the understanding and knowledge of the concept of the moratorium carried out and the impact on the population in the district of Seberang Perai. The results also show a high level of understanding of the concept of moratorium and also bring some positive effects to consumers and respondents. Thus, the results of this study can answer all the objectives by the respondents that I have distributed survey questions on the concept of moratorium and the impact on borrowers in the district of Seberang Perai, Penang.